Association between guidelines and medical practitioners’ perception of best management for patients attending with an apparently uncomplicated acute sore throat: A cross-sectional survey in five countries - Gunnarsson, Ronny (University of Gothenburg, 2020)
The aim was to investigate the relationship between guidelines and the medical practitioners’ perception of optimal care for patients attending with an apparently uncomplicated acute sore throat in five countries (Australia, Germany, Sweden, UK and USA).

Raw data are uploaded as an SPSS file as well as .csv. Descriptive labels and descriptions of values are found within the data file and in the PDF documentation. A scanned survey sheet is also provided along with notes on how it was coded at data entry.

Syftet var att undersöka sambandet mellan medicinska riktlinjer och läkares uppfattning om bästa omhändertagande av patienter som söker för okomplicerad faryngotonsillit (halsfluss). Undersökningen genomfördes i fem länder (Australien, Tyskland, Sverige, Storbritannien och USA).

Rådata finns i SPSS-format och som .csv. Beskrivning av varje variabel och dess värden finns i SPSS-filen men också i separat PDF-fil. Den inskannade enkäten medföljer med anteckningar om hur den kodades vid datainmatning.
Sambandet mellan guidelines och läkares uppfattning om optimalt handläggande av patienter med okomplicerad faryngotonsillit: En enkätstudie i fem länder
Keywords: Tonsillitis; Halsfluss; Guideline; Riktlinje [Publikationstyp]; Practice Guideline; Klinisk riktlinje [Publikationstyp]; Guideline Adherence; Följsamhet gentemot riktlinjer; Acute tonsillitis; Akut tonsillit (tonsillinflammation); General Medicine; Allmänmedicin